(untitled) (Bulletin KNOB, 2003)
Association De Terebinth is an association for funerary culture in the Netherlands, which asserts the values of final resting-places and the way in which death and everything it entails are dealt with. Funerary culture is a complex subject that can be studied from various perspectives. A lot of research is being done, but the stress lies chiefly on the immaterial aspect. The researches carried out are usually focused on familiar and obvious elements, such as cultural-technical and financial management of cemeteries or descriptions of what is to be seen at those cemeteries. So far, there has been relatively little research into the tangible aspects of funerary culture. A good national survey of the values of the disposal of the dead in general and of valuable cemeteries in particular is still lacking. The authorities did give the initial impetus to pay more attention to cultural-historically valuable cemeteries and sepulchral monuments, but this has not structurally resulted in more attention. Initiatives were notably developed without the authorities. These past years, for instance, a lot of popular-scientific publications appeared on the subject of death and the culture surrounding it. Applied research has also been carried out for the conservation of some interesting cemeteries. That not all research leads to a successful outcome probably has to do with the fact that it concerns a very unmanageable subject. In spite of various studies and management plans the old town cemetery on Spanjaardslaan in Leeuwarden continues to be at risk. The owner’s reluctance here is the reason why the decline can just go on. Only these last few years has the Netherlands Department for Conservation paid some attention to the subject. Not by carrying out research into the correct framework for this subject or an acceptable policy, but more practically by answering the many questions of the people involved in connection with protected funerary heritage. In the meantime about 1100 components or complete cemeteries of the approximately 4500 cemeteries or churchyards in the Netherlands have been placed on the government list. It is to be deduced from a recent research into 25 protected cemeteries that protection of a cemetery does not invariably contribute to its conservation. This probably has to do with the fact that in the past it was frequently only evaluative research that was carried out, selecting, describing, evaluating and protecting a number of top pieces at a 19th-century cemetery. Often there was no sequel to it, because of the very lack of policy referred to above. Fortunately, there is an increasing number of researchers who want to look at the funerary heritage from a wider perspective and who are also carrying out relevant research for this purpose in co-operation with the organisations and authorities concerned. Only in that way can conservation and development of funerary heritage proceed properly. After all, a cemetery consists of more than just art-historical aspects! In the future De Terebinth would like to contribute to a better-founded research into the funerary heritage, which is also the reason why the association is taking part in the Platform Mariaplaats.